Amylmetacresol and 2,4-dichlorobenzyl alcohol (AMC/DCBA) lozenge for postoperative sore throat: systematic review - Jitpreeda, Kittiya; Boonasa, Kiattida; Sirirattanakul, Pijak; Kesonsombat, Rattanapa (The Clinical Academia, 2019)
BACKGROUND Amylmetacresol and 2,4-dichlorobenzyl alcohol (AMC/DCBA) or Strepsils® lozenge is used for reducing severity score of sore throat in postoperative sore throat (POST) with no evidence from systematic and meta-analysis. METHODS Four independent reviewers systematically searched through electronic databases including Medline, Cochrane Library, Trip Database, Scopus and ClinicalTrials.gov using the keywords (operative OR extubation OR intubation OR “postoperative sore throat” OR POST) AND "sore throat" AND ("Amylmetacresol and 2,4-dichlorobenzyl alcohol" OR “AMC/DCBA” OR “Strepsils” OR lozenge). The search was confined to human studies without language restrictions. We also sought for additional studies using a hand searching to explore other unidentified studies outside the database to identify all relevant randomized controlled trials. We assessed the quality of the included studies using Jadad score and The Cochrane Collaboration’s Tool for Assessing Risk of Bias. Meta-analysis was performed where appropriate. RESULTS Two included randomized control trials involving 245 participants compared preoperative administration of AMC/DCBA lozenge (N=123) versus placebo (N=122) in patients with POST. This systematic review showed effect of AMC/DCBA lozenge on POST severity score (severity score grading; 0 to 3) compared to placebo within 30 minutes after operation (mean difference (MD) -0.36, 95% confidence interval (CI) -0.5 to -0.21; I2=0%) and at 24 hours after operation (MD -0.26, 95% CI -0.52 to -0.01; I2=79%). CONCLUSIONS Preoperative administration of AMC/DCBA lozenge significantly reduced POST severity score within 30 minutes after operation more than that of placebo. However, its effects at 24 hours after operation could not be concluded due to high heterogeneity.